Femal eperception: advantages and disadvantages of virtual shopping - Ríos Quintana, Yeily Marcela; Moreno Mendoza, Edward Fabian; Pineda López , Cindy Paola (Universidad Francisco de Paula Santander, 2017)
At the moment of buying on the Internet there are some types of factors that influence the process since the client establishes an indirect evaluation with his specific criteria to know if the company and the product totally fulfills and satisfies his expectations and in this way generates confidence to execute his acquisition. Online shopping not only benefits the buyers, but also the sellers, more so in times where virtual dynamics is a trend. The results of this descriptive research with a quantitative approach applied to the students of the Business Administration program were used to identify advantages and disadvantages of making purchases over the Internet. Conclusion: Women are interested in the development of virtual shopping in spite of not interacting with the product. On the other hand, connectivity and distrust (loss of money) are the main disadvantages in e-commerce.